2020
DOI: 10.1177/1745506519895175
|View full text |Cite
|
Sign up to set email alerts
|

Bio-mechanical risk factors for uterine prolapse among women living in the hills of west Nepal: A case-control study

Abstract: Objective: To investigate whether heavy load carrying, wearing a patuka, and body position at work are risk factors for uterine prolapse among Nepali women. Methods: Community-based case-control study of 448 women (170 cases of uterine prolapse; 278 controls) aged 18–60 years in Kaski district, Nepal was conducted. Women diagnosed with uterine prolapse were cases. Two controls were recruited for each case, frequency-matched by residential area and age. Multivariate logistic regression was used to investigate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 19 publications
0
15
2
2
Order By: Relevance
“…This may indicate that there is no association between heavy load-carrying activities and POP or that the sample sizes were insufficient. A recent community-based case control study in Nepal, for example, did not identify an association between load-carrying duration (at least 12 hours in the last week) or frequency (almost every day, sometimes, not at all) and uterine prolapse confirmed by pelvic examination [21]. However, that study would have involved generally lighter loads than were carried by the sand mining women in the present study.…”
Section: Discussioncontrasting
confidence: 66%
“…This may indicate that there is no association between heavy load-carrying activities and POP or that the sample sizes were insufficient. A recent community-based case control study in Nepal, for example, did not identify an association between load-carrying duration (at least 12 hours in the last week) or frequency (almost every day, sometimes, not at all) and uterine prolapse confirmed by pelvic examination [21]. However, that study would have involved generally lighter loads than were carried by the sand mining women in the present study.…”
Section: Discussioncontrasting
confidence: 66%
“…Regarding the study area of the articles; two studies in Ethiopia [ 37 , 38 ], one study in Tanzania [ 39 ],one study in United Arab Emirates [ 40 ], four studies in USA [ 41 44 ], three studies in Sweden [ 14 , 45 , 46 ], one study in UK [ 47 ], one study in New Zeeland [ 48 ], and one study in Nepal [ 49 ] were included. As far as the study design of the included articles concerned, we included seven studies case control [ 37 39 , 43 , 45 , 46 , 49 ], three cohort [ 14 , 47 , 48 ], two cross sectional [ 40 , 44 ] and two RCT [ 41 , 42 ] studies. Concerning the POP measurement in the included articles, seven studies measured POP objectively [ 37 , 39 , 41 43 , 48 , 49 ] and the remaining seven measured subjectively [ 14 , 38 , 40 , 44 47 ] (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…As far as the study design of the included articles concerned, we included seven studies case control [ 37 39 , 43 , 45 , 46 , 49 ], three cohort [ 14 , 47 , 48 ], two cross sectional [ 40 , 44 ] and two RCT [ 41 , 42 ] studies. Concerning the POP measurement in the included articles, seven studies measured POP objectively [ 37 , 39 , 41 43 , 48 , 49 ] and the remaining seven measured subjectively [ 14 , 38 , 40 , 44 47 ] (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…According to mainly anthropologic research, women experiencing POP in developing countries frequently report heavy load carrying and strenuous physical labor during the postpartum period as perceived causes of POP [5,7,18]. In the few relevant studies conducted to date, load carrying has been identified as a risk factor for POP in some settings [19,20], but not in others [21]. A sample of women in Tanzania carrying heavy objects for ≥ 2 hours per day had almost 5 times the odds of POP compared to those who did not carry heavy objects (95% CI: 1.7-13.2) [20], while carrying heavy objects for at least 12 hours a week was not a risk factor for POP among a sample of women in Nepal [21].…”
Section: Introductionmentioning
confidence: 99%
“…In the few relevant studies conducted to date, load carrying has been identified as a risk factor for POP in some settings [19,20], but not in others [21]. A sample of women in Tanzania carrying heavy objects for ≥ 2 hours per day had almost 5 times the odds of POP compared to those who did not carry heavy objects (95% CI: 1.7-13.2) [20], while carrying heavy objects for at least 12 hours a week was not a risk factor for POP among a sample of women in Nepal [21]. This may reflect varied characteristics of load carrying by women including the weight of the load, the load carrying duration (determined by distances travelled), and the frequencies of load carrying.…”
Section: Introductionmentioning
confidence: 99%